2022
DOI: 10.1038/s41396-022-01300-0
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen cycling and microbial cooperation in the terrestrial subsurface

Abstract: The nitrogen cycle plays a major role in aquatic nitrogen transformations, including in the terrestrial subsurface. However, the variety of transformations remains understudied. To determine how nitrogen cycling microorganisms respond to different aquifer chemistries, we sampled groundwater with varying nutrient and oxygen contents. Genes and transcripts involved in major nitrogen-cycling pathways were quantified from 55 and 26 sites, respectively, and metagenomes and metatranscriptomes were analyzed from a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 104 publications
2
30
0
Order By: Relevance
“…The conservation of both ligand-binding and Ca 2+ -coordinating residues in the group of 610 amidase-associated uncharacterized proteins from the SSN used to identify Me Ami suggests a shared biochemical requirement for amino acid amides in the species from which these genes were identified. The prevalence of Gram-negative nitrogen-fixing soil bacteria within this group, some of which are known to thrive on short chain amines, suggests an evolutionary advantage for soil bacteria capable of catalyzing amidase reactions on l -amino acid amides. This would metabolize them to the respective l -amino acid and ammonia, facilitating access to amino acid utilization pathways such as the citric acid cycle and ammonia assimilation pathways such as the glutamine synthetase–glutamate synthase pathway .…”
Section: Discussionmentioning
confidence: 99%
“…The conservation of both ligand-binding and Ca 2+ -coordinating residues in the group of 610 amidase-associated uncharacterized proteins from the SSN used to identify Me Ami suggests a shared biochemical requirement for amino acid amides in the species from which these genes were identified. The prevalence of Gram-negative nitrogen-fixing soil bacteria within this group, some of which are known to thrive on short chain amines, suggests an evolutionary advantage for soil bacteria capable of catalyzing amidase reactions on l -amino acid amides. This would metabolize them to the respective l -amino acid and ammonia, facilitating access to amino acid utilization pathways such as the citric acid cycle and ammonia assimilation pathways such as the glutamine synthetase–glutamate synthase pathway .…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains unclear if the major energy source to sustain cell metabolism originated from complete ammonium oxidation or rather from nitrite oxidation. In fact, a recent subsurface study detected transcriptional activity in association with nitrite oxidation but not ammonium oxidation for a CMX-related MAG [65], while CMX Nitrospira in water from rapid sand filters did not prefer to oxidize external nitrite alone [7]. As we found NO 2 - transporters in representative groundwater MAGs from both CMX clades, the cells may also be capable of taking up the NO 2 - formed by AOB, supporting their primary role as nitrite oxidizers along with Nitrosomonas ureae and Nitrosospira sp.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, we did find changes in the abundance of N‐cycling genes along the Damma glacier forefield: OD&S dominated N‐cycling processes during the process of soil development, genes involved in nitrogen fixation were more abundant in the vegetated soils, and genes related to nitrification were enriched in the barren soils. Despite having distinct requirements (e.g., for oxygen), many reactions in the N‐cycle tend to co‐occur in the environment, leading to efficient N recycling, competition for the same resource (e.g., nitrate) and coupled processes, such as nitrification and denitrification (Mosley et al, 2022). Brankatschk et al (2011) suggested, however, that the number of genes involved in major N‐cycling pathways may not be consistent with the corresponding enzyme activity, so a deeper understanding of N‐cycling genes at the transcriptional and translational level may still be necessary in the Damma glacier forefield.…”
Section: Discussionmentioning
confidence: 99%